2012
DOI: 10.1097/jgp.0b013e31823e2fce
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives on the Benefits of Psychotherapy for Late-Life Depression

Abstract: Objectives: The future of psychotherapy research lies in the development of easy-to-use, efficient treatments that target specific characteristics and needs of patients with a given disorder. Meeting this aim will involve understanding why people seek psychotherapy and the therapeutic features that they feel are most helpful in their recovery. Identifying key features of treatment that patients feel lead to improvement may help identify the active ingredients of psychotherapy and further refine treatment. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 1 publication
0
19
0
1
Order By: Relevance
“…Focusing on those interactional skills related to better outcome may be helpful in both training and research (van Os et al ., 2019). Furthermore, including patients in the evaluation of treatments may help to enhance efficacy and to identify what is helpful, less helpful, or even harmful (Dakin and Arean, 2013). In this way, treatment manuals may be improved on the basis of systematic patient feedback.…”
Section: Improving Available Treatments: Tailoring the Treatment Morementioning
confidence: 99%
“…Focusing on those interactional skills related to better outcome may be helpful in both training and research (van Os et al ., 2019). Furthermore, including patients in the evaluation of treatments may help to enhance efficacy and to identify what is helpful, less helpful, or even harmful (Dakin and Arean, 2013). In this way, treatment manuals may be improved on the basis of systematic patient feedback.…”
Section: Improving Available Treatments: Tailoring the Treatment Morementioning
confidence: 99%
“…La psychothérapie du sujet âgé peut néanmoins nécessiter quelques adaptations dans le sens d'une plus grande flexibilité du cadre thérapeutique [27]. Les thérapies de groupe s'avèrent particulièrement adaptées, car elles permettent au sujet âgé déprimé, centré sur ses difficultés, de prendre un certain recul vis-à-vis de luimême, de se décentrer, tout en favorisant une reprise de contact avec ses pairs.…”
Section: L'approche Psychothérapeutiqueunclassified
“…Older adults’ positive therapy engagement experiences have been found to be associated with the perceived benefits provided by psychological therapies that have specific working mechanisms (Camacho et al., 2018; Choi et al., 2013; Dakin & Areán, 2013; Nance, 2012; Simmonds et al., 2013; Williams et al., 2018). Older adults thought that self‐help groups were beneficial because the groups provided opportunities to interact with other older adults with depression (Stark et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In studies that used PST and counselling, older adults reported the benefits of developing specific coping strategies to address mental health problems (Barg et al., 2010; Camacho et al., 2018; Choi et al., 2013; Dakin & Areán, 2013). These strategies enabled older adults to manage their depressive symptoms in daily life, as described in the following quotes:
It [problem‐solving therapy] helped me get a greater understanding of my depression and how to work on it.
…”
Section: Resultsmentioning
confidence: 99%